KEPUASAN PELANGGAN MEMEDIASI PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP LOYALITAS PELANGGAN - Novianti Novianti; Endri Endri; Darlius Darlius (Universitas Mercu Buana, 2018)
Abstract. This study aims to examine the effect of service quality and promotiondirectly to customer satisfaction and customer loyalty. This study also examines theinfluence of service quality and promotion indirectly to customer loyalty throughcustomer satisfaction. The study was conducted on 175 customers of Cikarang MedikaFarma Pharmacy taken with simple random sampling technique and given questionnaire72 statement with Likert Scale to measure response to research variables. After testingthe validity and reliability, as well as the prerequisite test, conducted path analysis testusing software Lisrel 8.80. The results showed that there was a significant direct effectbetween service quality and promotion on customer satisfaction as well as on customerloyalty. Service quality also has a positive and significant indirect impact on customerloyalty through customer satisfaction. Promotion has a positive and significant indirecteffect on customer loyalty through customer satisfaction.